Individual Counseling Guide Rational Emotive Behavior Therapy Approach Self-Talk Technique for Guidance and Counseling Teachers - Romiaty; Fendahapsari Singgih Sendayu; Nonsihai; Nopi Feronika; Herda Fitri Br Ginting (Universitas Islam Negeri Madura, 2025)
Individual counseling services are services to help solve student problems. One approach that can help students is the Rational Emotive Behavior Therapy (REBT) counseling approach, the Self-Talk technique. However, this approach is not used by Guidance and Counseling (BK) teachers; therefore, BK teachers in high school should have a complete guide to implement this approach. This research aims to develop an individual counseling guide using the REBT Self-Talk technique approach for high school guidance and counseling teachers in Palangka Raya. The research method in this study uses the development method or Research and Development (R&D). This development research procedure uses a 4D (four D) model, namely Define, Design, Development, Disseminate. The population of this study was high school guidance and counseling teachers in Palangka Raya City, totaling 30 people. Data collection techniques include interviews, questionnaires, and documentation. Data analysis techniques use quantitative and qualitative. The research results show that the guide has been validated and has received assessments from expert testers. Media experts with an accumulated feasibility value of 1,109 are calculated based on a high coefficient value, which means they are suitable for use. Material experts with an accumulated feasibility value of 0.945 are calculated based on the high coefficient values which is high, which means feasible. Practitioner experts have an accumulated feasibility value of 1.16 which is declared suitable for use. They have carried out a small group test with the calculated value resulting in an effect size of 0.904, so it can be concluded that the test has high effect criteria. The limitation of this research is that it was only tested on a small group and not on a large group.